Riesgo Crediticio de la Cooperativa de Ahorro y Crédito “San Antonio” Ltda. Vinces - Mendoza Carriel, Nora Liseth (2017)
The financial businesses are a very vital part for the growth of all the countries, however in Ecuador the companies that suffer more solvency problems are the credit, in many occasions it is due to the lack of revision of the sources of destined economic income for the payment. This case study investigates the Credit Risk of the "San Antonio" Cooperative of Savings and Loans Ltda. Vinces, where it is observed that there is a lack of tools and inadequate methodology in the measurement of credit personnel performance, which generates deficiency in the achievement of budget and objectives. It is considered necessary to design control techniques, so that it helps with the portfolio rotation and thus the degree of indebtedness decreases, determining risks for this must be carried out an efficient and effective management to be able to carry out a better control of them. At present it is very important for financial institutions to have adequate procedures in the policies used in the granting of credits, exercising an effective control over collections and credits. This research was carried out as a preliminary step to obtain the title of Engineering in Accounting and Auditing, and follows the research lines of the Financial Management and Social Engagement career. The methodology used in this case study was descriptive, and the technique was interviews with the agency manager and credit counselor, where it was observed that there are limitations corresponding to the functions that they develop.